Exposed: the toxic chemistry of everyday products and what's at stake for American power - Schapiro, Mark (Vermont, 2007)
"Americans' confidence in their government-sanctioned environmental and consumer protections receives another blow in investigative reporter Schapiro's exposé, which explores such discomforting information as the 2005 U.S. Centers for Disease Control tests that found 148 toxic chemicals "in the bodies of 'Americans of all ages.'" The U.S.'s unique tendency to take no action against businesses and their products until a disaster occurs keeps them tied to 1970s standards-"exposed to substances from which increasing numbers of people around the world are being protected"-while "the principle of preventing harm before it happens, even in the face of imperfect scientific certainty," guides an increasing number of countries; by "creating legal and financial incentives," governments in Europe and Japan have kept citizens relatively safe from what contributes to the deaths "of at least 5 million people a year," according to the World Health Organization. Schapiro (co-author, with David Weir, of Circle of Poison: Pesticides and People in a Hungry World) discovers toxins in personal care products, toys, electronics and foods which are, in some cases, manufactured solely for U.S. consumption, and traces them to the people and events responsible. Though a look at growing support for change in the U.S. provides some hope, a guide to action would have been an appropriate addition to Schapiro's prescient muckraking."